Transition metal catalysts, processes for their preparation and use

CN117899873BActive Publication Date: 2026-10-27XIAMEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311754572.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-19
Publication Date
2026-10-27
Estimated Expiration
2043-12-19

AI Technical Summary

Technical Problem

[0007]本发明的主要目的是克服上述现有技术的至少一种缺陷,解决在反应体系中含有硫元素的催化加氢过程中,活性金属催化剂被毒化失活的问题

Benefits of technology

[0041]1.本发明提供的过渡金属催化剂为碳包覆过渡金属纳米颗粒,其中碳壳可以起到阻止硫物种与过渡金属纳米颗粒的直接接触,从而保护过渡金属纳米颗粒不被毒化,表现出良好的耐硫性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the field of catalysis, and provides a transition metal catalyst and a preparation method and application thereof. The carbon-coated transition metal nanoparticle catalyst is a core-shell structure with a composite shell layer and a core, the composite shell layer comprises carbon and a transition metal oxide layer, and the core is a transition metal nanoparticle. The catalyst has high stability in a nitro hydrogenation reaction system containing sulfur, the preparation process is simple, the catalyst is suitable for large-scale production, and has important industrial application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalysis technology, specifically to a method for preparing a transition metal catalyst and its application in the hydrogenation of sulfur-containing nitrate substrates. Background Technology

[0002] Aniline compounds and their derivatives play an important role in fine chemical intermediates. Currently, in industry, the corresponding amino products are mainly prepared by catalytic hydrogenation of nitro groups. However, the catalytic hydrogenation of nitro groups to amino groups produces intermediates such as nitrosamines, hydroxylamines, and azo compounds. These intermediates are not only difficult to detect and reduce reaction yields, but also present challenges in separation. In particular, the presence of carbon-carbon double bonds, carbonyl groups, halogens, carboxyl groups, hydroxyl groups, thioether groups, etc., in the substrate greatly increases the difficulty of selectively obtaining amino groups.

[0003] In the hydrogenation of halogenated aromatic nitro compounds, the nitro group and halogen compete for adsorption at active sites, leading to the activation and desorption of the halogen and a significant reduction in reaction selectivity. Furthermore, the electron-rich amino group transfers electrons to the halogen, increasing the electron cloud density of the halogen group and weakening the carbon-halogen bond, making it easier for the halogen to desorb. Simultaneously, the desorbed halogen can poison the catalyst, reducing its lifespan. Besides the hydrogenation of halogen-containing nitro compounds, the hydrogenation of sulfur-containing nitro compounds is also a significant challenge. Both noble metal catalysts such as platinum and palladium and non-noble metal catalysts such as nickel and cobalt are highly sensitive to sulfur during hydrogenation. Sulfur-containing substances, such as S... 2- Thiols, thiophenes, etc., are extremely toxic and are very common in industrial production.

[0004] Currently, efforts are mainly focused on improving catalyst performance from two directions: active metal and support. Starting with the active metal surface, Okamoto et al. encapsulated Pd in ​​a block copolymer (PI) formed by styrene, 2-[2-(4-vinylphenyl)ethoxymethyl]ethylene oxide, tetraethylene glycol mono-2-phenyl-2-propenyl ether, and 2,2'-azobis(isobutyronitrile) using microencapsulation and cross-linking methods (PI-Pd). PI-Pd exhibits good resistance to sulfur species, and XRF analysis of the reaction mother liquor did not detect Pd leaching. Okamoto believes that the excellent activity of PI-Pd is due to the high dispersion of palladium in the polymer and the protection of palladium from sulfur poisoning by the benzene rings surrounding the polymer. However, due to the flexibility of the copolymer, Pd is difficult to maintain long-term sulfur resistance. [The Journal of Organic Chemistry, 2004, 69(8):2871-2873]

[0005] Starting with support modification, Yin et al. reported a zeolite-supported metal composite catalyst with a core-shell structure. They found that ZIF-8 / Pd / ZIF-8 exhibited better catalytic selectivity for 1-hexene than cis-cyclooctene, and the ZIF-8 shell effectively resisted sulfur poisoning by thiophene (0.46 nm). [Catalysis Today, 2016, 265(2): 203-209] Wang et al. used azeotropic distillation to highly disperse palladium nanoparticles in situ within ZSM-5 (Pd / ZSM-5-IS). Using the hydrogenation of p-nitrophenol to p-aminophenol as a model reaction, they investigated the sulfur poisoning resistance of the catalyst using thiophene and 4,6-dimethyldibenzothiophene as sulfur sources. However, H2S (0.36 nm), with a smaller kinetic diameter, could still significantly deactivate this type of catalyst. [ChemicalEngineering Journal, 2016, 283(1): 922-928]

[0006] The industrial production of highly selective and stable catalysts for nitro hydrogenation remains challenging. In actual industrial catalytic processes, pretreatment of the hydrogenation feedstock is necessary to remove sulfur-containing compounds and prevent catalyst poisoning. However, trace amounts of sulfur are unavoidable, and the desulfurization process increases production costs. Furthermore, halogen loss can severely impact equipment lifespan. Moreover, when the catalytic feedstock itself contains sulfur, even higher requirements are placed on the catalyst's sulfur resistance. Therefore, the development and application of highly efficient nitro hydrogenation catalysts remains a significant challenge. Summary of the Invention

[0007] The main objective of this invention is to overcome at least one of the defects of the prior art and solve the problem of poisoning and deactivation of active metal catalysts in catalytic hydrogenation processes containing sulfur in the reaction system. On one hand, it provides a transition metal catalyst; on the other hand, it provides a method for preparing the transition metal catalyst; and still another hand, it provides the application of the transition metal catalyst in the hydrogenation of sulfur-containing nitrate substrates.

[0008] The present invention provides the following technical solutions to achieve the above objectives:

[0009] A transition metal catalyst includes a core-shell structure having a composite shell and a core, wherein the composite shell comprises a carbon shell and a transition metal oxide layer, and the core is a transition metal nanoparticle. The transition metal nanoparticles contain either a carbon layer or a transition metal oxide layer.

[0010] In some embodiments, based on the total mass of the transition metal catalyst, the transition metal content in the catalyst is about 10 wt%-90 wt%, or about 20 wt%-80 wt%, or about 30 wt%-70 wt%, or about 40 wt%-60 wt%; the transition metal oxide content is about 1 wt%-5 wt%, and the carbon content is about 9 wt%-85 wt%.

[0011] In some embodiments, the diameter of the transition metal nanoparticles is about 2 to about 20 nm, preferably 5 to 15 nm.

[0012] In some embodiments, the transition metal nanoparticles are selected from one or more of iron, cobalt, nickel, and / or copper, preferably nickel.

[0013] In some embodiments, the transition metal nanoparticles are nickel, including zero-valent nickel and positive-valent nickel.

[0014] In some embodiments, the positive-valent nickel element is a +2 valent nickel element and / or a +1 valent nickel element.

[0015] In some embodiments, in the X-ray photoelectron spectroscopy spectrum of the catalyst, the Ni2p of the zero-valent nickel element... 3 / 2 The binding energy is 850eV-852eV, preferably 851.4eV.

[0016] In some embodiments, in the X-ray photoelectron spectroscopy spectrum of the catalyst, the Ni2p of the positive-valent nickel element... 3 / 2 The binding energy is 852eV-855eV, preferably 853.8eV.

[0017] In some embodiments, the carbon shell is selected from one or more of activated carbon, graphitic carbon, and graphene.

[0018] In some embodiments, the thickness of the carbon shell is 0.1-5 nm, preferably 0.3-2 nm.

[0019] On the other hand, a method for preparing a transition metal catalyst is provided, comprising the following steps:

[0020] (1) Weigh out a certain molar ratio of transition metal precursor and organic carbon source precursor and dissolve them in a solvent to form a homogeneous solution.

[0021] (2) The homogeneous solution obtained in step 1) is heated to remove the solvent, and the precursor solid is then ground into powder.

[0022] (3) The precursor powder obtained in step 2) is calcined and reduced at high temperature under an inert or reducing atmosphere to obtain a transition metal catalyst.

[0023] (4) The reduced transition metal catalyst obtained in step 3) is oxidized at high temperature in an oxidizing atmosphere to obtain a transition metal catalyst.

[0024] In some embodiments, the transition metal precursor in step 1) is selected from one or more transition metal oxides, transition metal salts, and transition metal bases.

[0025] In some embodiments, the organic carbon source in step 1) is selected from one or more of ethylenediamine, dicyandiamide, malic acid, citric acid, ethylenediaminetetraacetic acid, glucose, and pyromellitic acid.

[0026] In some embodiments, the solvent in step 1) is selected from one or more of methanol, ethanol, toluene, and water.

[0027] In some embodiments, the molar concentration of the transition metal precursor in step 1) is 0.1-1 mol / L, preferably 0.3-0.6 mol / L, and the molar ratio of the transition metal precursor to the organic carbon source precursor is 1:0.5-1:4, preferably 1:1-1:2.

[0028] In some embodiments, the heating temperature in step 2) is 60-150°C, preferably 90-130°C.

[0029] In some embodiments, the atmosphere in step 3) is selected from one or more of nitrogen, argon, hydrogen, carbon monoxide, and a 5% hydrogen-argon mixture. The calcination temperature is 500-850°C or 600-750°C, and the calcination time is 2-4 hours.

[0030] In some embodiments, the oxidizing atmosphere in step 4) is selected from one or more of oxygen, air, and a 50% oxygen-nitrogen mixture. The oxidation temperature is 50-150°C, preferably 70-130°C, and the oxidation time is 1-480h, preferably 24-240h.

[0031] On the other hand, it provides the application of transition metal catalysts in the hydrogenation of nitro aromatic compounds. Nitro aromatic compounds and transition metal catalysts react with hydrogen in a reaction solvent to obtain sulfur-containing amino products.

[0032] In some embodiments, the molar ratio of the transition metal catalyst to the sulfur-containing nitrate substrate is 1:10-1:100, preferably 1:20-1:70.

[0033] In some embodiments, the nitro-containing aromatic compound has the general formula shown in formula (I):

[0034]

[0035] Among them, (R) nThis indicates that each of the n H atoms on the benzene ring is independently replaced by n identical or different R substituents, where n is 0, 1, 2, 3, 4, or 5.

[0036] R is selected from nitro, amino, halogen, hydroxyl, alkyl, alkoxy, aldehyde, thioether or thiol.

[0037] The compounds of formula (I) include one or more of nitrobenzene, o-dinitrobenzene, o-nitroaniline, p-dinitrobenzene, p-nitroaniline, m-dinitrobenzene, m-nitroaniline, o-chloronitrobenzene, m-chloronitrobenzene, p-chloronitrobenzene, 4-nitroanisole, 2-nitro-5-phenylmercaptoaniline, 2-nitrodiphenyl sulfide, bis(2,4-dinitrobenzene)disulfide, 3,3-dinitrobenzene disulfide, (4-bromophenyl)(4-nitrophenyl) sulfide, 3-nitroanisole and / or (2,4-dimethylphenyl)(2-nitrophenyl)sulfane.

[0038] In some embodiments, the reaction solvent is selected from one or more of methanol, ethanol, isopropanol, and toluene.

[0039] In some embodiments, the pressure of the hydrogenation reaction is 0.8-4 MPa, preferably 1.5-3 MPa, and the reaction temperature is 60-120°C.

[0040] According to the above technical solution, the present invention has at least one of the following beneficial effects:

[0041] 1. The transition metal catalyst provided by the present invention is carbon-coated transition metal nanoparticles, wherein the carbon shell can prevent sulfur species from directly contacting the transition metal nanoparticles, thereby protecting the transition metal nanoparticles from poisoning and exhibiting good sulfur resistance.

[0042] 2. A transition metal precursor and an organic carbon source precursor are dissolved in a solvent and heated to undergo hydrolysis and condensation reactions, forming a homogeneous system. High-temperature calcination yields a nanoparticle catalyst with uniform size. After calcination, the transition metal catalyst is heated in an oxygen-containing atmosphere for oxidation, causing an oxide layer to form on the surface of the exposed transition metal nanoparticles that are not completely encapsulated by carbon.

[0043] 3. The preparation process of this invention is simple, green and pollution-free throughout the entire process, and has universal applicability. It can be used for large-scale industrial production and has important industrial application value.

[0044] 4. In the hydrogenation of nitro substrates, the carbon shell serves to transfer overflow hydrogen and prevent direct contact between sulfur species and transition metal nanoparticles. Therefore, this carbon-encapsulated transition metal catalyst exhibits stable catalytic performance in both sulfur-containing substrate hydrogenation systems and substrate hydrogenation systems containing sulfur impurities. Furthermore, for substrate hydrogenation systems containing sulfur impurities, this catalyst can effectively reduce the cost associated with substrate pretreatment.

[0045] Terminology Explanation

[0046] In the description of this specification, references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Attached Figure Description

[0047] The following figures are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof.

[0048] Figure 1 This is the X-ray diffraction (XRD) pattern of catalyst A in Example 1.

[0049] Figure 2 This is a transmission electron microscope (TEM) image of catalyst A prepared in Example 1.

[0050] Figure 3 This is a transmission electron microscope (TEM) image of catalyst A prepared in Example 2.

[0051] Figure 4 This is the X-ray photoelectron spectroscopy (XPS) spectrum of catalyst A in Example 1.

[0052] Figure 5 This is the in-situ carbon monoxide adsorption infrared spectrum of catalyst A in Preparation Example 1 (pretreatment conditions: temperature 150℃, time 1h).

[0053] Figure 6 This is the in-situ carbon monoxide adsorption infrared spectrum of catalyst A in Preparation Example 1 (pretreatment conditions: temperature 400℃, time 1h).

[0054] Figure 7 This is the nitrogen adsorption-desorption isotherm (BET) curve for preparing catalyst A in Example 1. Detailed Implementation

[0055] The following provides various embodiments or examples to enable those skilled in the art to implement the invention based on the description. These are merely examples and not intended to limit the invention. The endpoints and values ​​of the ranges disclosed herein are not limited to precise ranges or values; these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, endpoint values ​​of various ranges, endpoint values ​​of various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0056] Preparation Example 1

[0057] This embodiment illustrates a method for preparing a transition metal catalyst.

[0058] Weigh out 30 mmol of nickel hydroxide and 30 mmol of citric acid, dissolve them separately in 100 ml of deionized water, stir vigorously until a homogeneous solution is obtained, and continue heating to evaporate the solvent. Once a viscous liquid is formed, place it in a drying oven and evaporate it completely to dryness. Then, grind the resulting solid into powder to obtain precursor A. The precursor A powder is then calcined at 500 °C under a nitrogen atmosphere to obtain calcined product A. Finally, calcined product A is placed in air for oxidation for 24 hours to obtain catalyst A.

[0059] Figure 1 The XRD pattern of catalyst A shows obvious Ni face-centered cubic diffraction peaks. Figure 2 This is a TEM image of catalyst A. It shows a uniform layer of carbon coating on the catalyst surface, with a thickness of 0.5-2 nm. The catalyst itself has a size of 5-15 nm and is evenly distributed. Figure 4 This is the XPS plot of catalyst A. It can be seen that the proportion of high-valence Ni in the catalyst increases significantly after oxidation treatment. Figure 5 The image shows the in-situ carbon monoxide adsorption infrared spectrum of catalyst A (pretreatment conditions: temperature 150℃, time 1h). It can be seen that there is no chemisorption of carbon monoxide on the Ni surface, indicating that there is no Ni surface exposed. Figure 6 The image shows the in-situ carbon monoxide adsorption infrared spectrum of catalyst A (pretreatment conditions: temperature 400℃, time 1h). The chemisorption of carbon monoxide on the Ni surface is clearly visible, indicating that the nickel oxide on the catalyst surface is reduced by hydrogen, thus proving the presence of an oxide layer on the catalyst surface. Inductively coupled plasma atomic absorption spectrometry (ICP-AES) analysis shows that catalyst A contains 84% ​​nickel and nickel oxide, and 16% carbon.

[0060] Preparation Example 2

[0061] This embodiment illustrates another method for preparing a transition metal catalyst.

[0062] Weigh out 50 mmol of nickel hydroxide and 75 mmol of malic acid, dissolve them separately in 150 ml of deionized water, stir vigorously until a homogeneous solution is obtained, and continue heating to evaporate the solvent. Once a viscous liquid is formed, place it in a drying oven and evaporate it completely to dryness. Then, grind the resulting solid into powder to obtain precursor B. The precursor B powder is then calcined at 550 °C under a nitrogen atmosphere to obtain calcined product B. Finally, calcined product B is placed in air for oxidation for 6 hours to obtain catalyst B.

[0063] Figure 3 This is a TEM image of catalyst B. The catalyst surface is uniformly coated with a layer of carbon, with a thickness of 0.5-2 nm. The catalyst size is 5-15 nm, and the carbon layer is uniformly distributed. Inductively coupled plasma atomic emission spectrometry (ICP-AES) analysis shows that catalyst B contains 78% nickel and nickel oxide, and 22% carbon. The metal and carbon contents are mainly calculated using ICP-AES; the oxide layer content is currently calculated based on literature and experiments.

[0064] Preparation Example 3

[0065] This embodiment illustrates another method for preparing a transition metal catalyst.

[0066] Weigh out 50 mmol of copper hydroxide and 75 mmol of citric acid, dissolve them separately in 150 ml of deionized water, stir vigorously until a homogeneous solution is obtained, and continue heating to evaporate the solvent. Once a viscous liquid is formed, place it in a drying oven and evaporate it completely to dryness. Then, grind the resulting solid into powder to obtain precursor C. The precursor C powder is then calcined at 550 °C under a nitrogen atmosphere to obtain calcined product C. Finally, the calcined product C is placed in air for oxidation for 6 hours to obtain catalyst C.

[0067] Preparation Example 4

[0068] This embodiment illustrates another method for preparing a transition metal catalyst.

[0069] Weigh out 50 mmol of cobalt hydroxide and 75 mmol of citric acid, dissolve them separately in 150 ml of deionized water, stir vigorously until a homogeneous solution is obtained, and continue heating to evaporate the solvent. Once a viscous liquid is formed, place it in a drying oven and evaporate it completely to dryness. Then, grind the resulting solid into powder to obtain precursor D. The precursor D powder is then calcined at 550 °C under a nitrogen atmosphere to obtain calcined product D. Finally, calcined product D is placed in air for oxidation for 6 hours to obtain catalyst D.

[0070] Example 5

[0071] Application of the transition metal catalyst in Example 1 in the hydrogenation of a halogenated nitro compound: 0.1 g of catalyst A, 1 g of o-nitroaniline, and 15 ml of methanol were placed in a 50 ml high-pressure reactor liner. The temperature was increased to 90 °C at 5 °C / min, and the hydrogenation reaction was carried out under a hydrogen pressure of 2.5 MPa. Before the reaction, the air in the reactor was replaced with nitrogen. After 40 min of reaction, heating and stirring were stopped. After cooling to room temperature, the pressure was released, the reactor was opened, and the reaction mixture was taken out. High-performance liquid chromatography analysis showed that the conversion rate of o-nitroaniline was 100%, and the selectivity was 99.5%. See Table 2 for details.

[0072] Example 6

[0073] Application of the transition metal catalyst in Preparation Example 1 in the hydrogenation of a sulfur-containing nitrate substrate: 0.1 g of catalyst A, 1 g of 4-nitroanisole, and 15 ml of methanol were placed in a 50 ml high-pressure reactor liner. The temperature was increased to 80 °C at 5 °C / min, and the hydrogenation reaction was carried out under a hydrogen pressure of 3.5 MPa. Before the reaction, the air in the reactor was replaced with nitrogen. After the reaction was completed, heating and stirring were stopped, and the reactor was allowed to cool to room temperature before depressurization. The reaction mixture was then opened and the reaction mixture was taken out for high-performance liquid chromatography analysis. The conversion rate of 4-nitroanisole was 99.4%, and the selectivity was 99.2%. The catalyst was reused 4 times without significant deactivation. Detailed results are shown in Table 1.

[0074] Example 7

[0075] This example illustrates the application of the transition metal catalyst from Preparation Example 2 in the hydrogenation of a sulfur-containing nitrate substrate.

[0076] 0.2 g of catalyst B, 2 g of 2-nitro-5-phenylmercaptoaniline, and 30 ml of methanol were placed in the lining of a 50 ml high-pressure reactor. The temperature was increased to 110 °C at 5 °C / min, and a hydrogenation reaction was carried out under a hydrogen pressure of 4 MPa. Before the reaction, the air in the reactor was replaced with nitrogen. After 40 min of reaction, heating and stirring were stopped. After cooling to room temperature, the pressure was released, the reactor was opened, and the reaction mixture was taken out for high-performance liquid chromatography analysis. The conversion rate of 2-nitro-5-phenylmercaptoaniline was 99.1%, and the selectivity was 99.4%. The catalyst was reused 3 times without significant deactivation. Detailed results are shown in Table 1.

[0077] Example 8

[0078] This example illustrates the application of the transition metal catalyst prepared in Example 1 in the hydrogenation of another sulfur-containing nitrate substrate.

[0079] 0.1 g of catalyst A, 1 g of 2-nitro-5-phenylmercaptoaniline, and 15 ml of methanol were placed in the lining of a 50 ml high-pressure reactor. The temperature was increased to 100 °C at 5 °C / min, and a hydrogenation reaction was carried out under a hydrogen pressure of 3 MPa. Before the reaction, the air in the reactor was replaced with nitrogen. After the reaction was completed, heating and stirring were stopped, and the reactor was allowed to cool to room temperature before depressurization. The reactor was then opened and the reaction mixture was taken out for high-performance liquid chromatography analysis. The conversion rate of 2-nitro-5-phenylmercaptoaniline was 99.2%, and the selectivity was 99.2%. The catalyst was reused 4 times without significant deactivation. Detailed results are shown in Table 1.

[0080] Example 9

[0081] This example illustrates the application of the transition metal catalyst prepared in Example 3 in the hydrogenation of a sulfur-containing nitrate substrate.

[0082] 0.1 g of catalyst C, 1 g of 2-nitro-5-phenylmercaptoaniline, and 15 ml of methanol were placed in the lining of a 50 ml high-pressure reactor. The temperature was increased to 100 °C at 5 °C / min, and a hydrogenation reaction was carried out under a hydrogen pressure of 3 MPa. Before the reaction, the air in the reactor was replaced with nitrogen. After 120 min of reaction, heating and stirring were stopped. After cooling to room temperature, the pressure was released, the reactor was opened, and the reaction mixture was taken out for high-performance liquid chromatography analysis. The conversion rate of 2-nitro-5-phenylmercaptoaniline was 99.1%, and the selectivity was 99.4%. The catalyst was reused 3 times without significant deactivation. Detailed results are shown in Table 1.

[0083] Example 10

[0084] This example illustrates the application of the transition metal catalyst prepared in Example 4 in the hydrogenation of a sulfur-containing nitrate substrate.

[0085] 0.1 g of catalyst D, 1 g of 2-nitro-5-phenylmercaptoaniline, and 15 ml of methanol were placed in the lining of a 50 ml high-pressure reactor. The temperature was increased to 100 °C at 5 °C / min, and a hydrogenation reaction was carried out under a hydrogen pressure of 3 MPa. Before the reaction, the air in the reactor was replaced with nitrogen. After the reaction was completed, heating and stirring were stopped, and the reactor was allowed to cool to room temperature before depressurization. The reactor was then opened and the reaction mixture was taken out for high-performance liquid chromatography analysis. The conversion rate of 2-nitro-5-phenylmercaptoaniline was 98.9%, and the selectivity was 98.7%. The catalyst was reused three times without significant deactivation. Detailed results are shown in Table 1.

[0086] Conversion rate and selectivity were calculated using high-performance liquid chromatography (HPLC). The reaction results were normalized. Conversion rate = c(A) / (c(A) + c(B)) × 100%, Selectivity = c(B) / (c(B) + c(C)) × 100%.

[0087] In the formula, c(A): reactant area, c(B): product area, and c(C): area of ​​other intermediate products.

[0088] Table 1. Reaction results of catalysts prepared in different examples.

[0089]

[0090]

[0091] Comparative Example 1

[0092] This comparative example illustrates the application of an activated carbon-supported nickel catalyst in the hydrogenation of a halogenated nitrate substrate. 5g of thoroughly dried activated carbon was weighed into a 100ml beaker A. 6.2g of nickel nitrate hexahydrate was dissolved in 10ml of ethanol and placed in a 50ml centrifuge tube A. The clear solution in centrifuge tube A was slowly added dropwise to beaker A using a disposable dropper. The beaker was then aged in air at 25℃ for 24 hours. Afterward, beaker A was dried in an oven at 80℃ to obtain precursor D. Finally, the obtained precursor D powder was calcined at 450℃ under a hydrogen atmosphere at a heating rate of 5℃ / min to obtain catalyst E.

[0093] 0.1 g of catalyst E, 1 g of o-nitroaniline, and 15 ml of methanol were placed in the lining of a 50 ml high-pressure reactor. The temperature was increased to 90 °C at a rate of 5 °C / min, and a hydrogenation reaction was carried out under a hydrogen pressure of 2.5 MPa. Before the reaction, the air inside the reactor was replaced with nitrogen. After 60 min of reaction, heating and stirring were stopped, and the reactor was allowed to cool to room temperature before depressurization. The reactor was then opened, and the reaction mixture was analyzed by high-performance liquid chromatography. The conversion rate of o-nitroaniline was 100%, and the selectivity was 89.1%. See Table 2 for details.

[0094] Table 2 shows the reaction results of the comparative catalysts.

[0095] Catalyst A (Example 5) 100% 99.5% Comparative Example 1 100% 89.1%

[0096] Comparative Example 2

[0097] This comparative example illustrates the application of a Raney nickel catalyst in the hydrogenation of a sulfur-containing nitrate.

[0098] Weigh out 0.1g of the completely deposited Raney nickel wet catalyst and wash it three times with 20ml of methanol to obtain catalyst F.

[0099] 0.1 g of catalyst F, 1 g of 2-nitro-5-phenylmercaptoaniline, and 15 ml of methanol were placed in the lining of a 50 ml high-pressure reactor. The temperature was increased to 100 °C at 5 °C / min, and a hydrogenation reaction was carried out under a hydrogen pressure of 2 MPa. Before the reaction, the air in the reactor was replaced with nitrogen. After the reaction was completed, heating and stirring were stopped, and the reactor was allowed to cool to room temperature before the pressure was released. The reactor was then opened and the reaction mixture was taken out for high-performance liquid chromatography analysis. The conversion rate of 2-nitro-5-phenylmercaptoaniline was 99.6%, and the selectivity was 99.4%. The catalyst was significantly deactivated in the second reaction. Detailed results are shown in Table 3.

[0100] Comparative Example 3

[0101] This comparative example illustrates the application of an activated carbon-supported nickel catalyst in the hydrogenation of a sulfur-containing nitrate substrate.

[0102] 0.1 g of catalyst E, 1 g of 2-nitro-5-phenylmercaptoaniline, and 15 ml of methanol were placed in the lining of a 50 ml high-pressure reactor. The temperature was increased to 100 °C at 5 °C / min, and a hydrogenation reaction was carried out under a hydrogen pressure of 3 MPa. Before the reaction, the air in the reactor was replaced with nitrogen. After 60 min of reaction, heating and stirring were stopped. After cooling to room temperature, the pressure was released, the reactor was opened, and the reaction product was taken out for high-performance liquid chromatography analysis. The conversion rate of 2-nitro-5-phenylmercaptoaniline was 99.1%, and the selectivity was 99.3%. The catalyst was significantly deactivated in the second reaction. Detailed results are shown in Table 3.

[0103] Table 3 shows the reaction results of the comparative catalysts.

[0104]

[0105] Although the above embodiments have been described, those skilled in the art, once they understand the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the above descriptions are merely embodiments of the present invention and do not limit the scope of patent protection of the present invention. Any equivalent structural or procedural transformations made using the content of the present invention's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the scope of patent protection of the present invention.

Claims

1. The application of a transition metal catalyst in the hydrogenation of nitro-containing aromatic compounds, characterized in that, include: Transition metal catalysts and nitro aromatic compounds undergo hydrogenation reactions with hydrogen in a reaction solvent; The preparation method of the transition metal catalyst includes the following steps: (1) Weigh out the transition metal precursor and the organic carbon source precursor and dissolve them in the solvent to form a homogeneous solution. The transition metal is selected from one or more of iron, cobalt, nickel or copper. (2) The homogeneous solution obtained in step (1) is heated at 60-150℃ to remove the solvent to obtain the precursor solid, and then ground into powder. (3) The precursor powder obtained in step (2) is calcined in an inert atmosphere or a reducing atmosphere to obtain a catalyst intermediate. The atmosphere is selected from one or more of nitrogen, argon, hydrogen and carbon monoxide. The calcination temperature is 400-1200℃ and the calcination time is 1-24 h. (4) The catalyst intermediate obtained in step (3) is oxidized in an oxidizing atmosphere to obtain the target catalyst; The oxidizing atmosphere is selected from one or more of oxygen, air, and a 50% oxygen-nitrogen mixture. The oxidation temperature is 20-300℃ and the oxidation time is 1-480 h.

2. The application according to claim 1, characterized in that, Step 1) The transition metal precursor is selected from one or more of transition metal oxides, transition metal salts and / or transition metal bases.

3. The application according to claim 1, characterized in that, The organic carbon source in step 1) is selected from one or more of ethylenediamine, dicyandiamide, malic acid, citric acid, ethylenediaminetetraacetic acid, glucose and / or pyromellitic acid; the solvent in step 1) is selected from one or more of methanol, ethanol, toluene and / or water.

4. The application according to claim 1, characterized in that, Step 1) The molar concentration of the transition metal precursor is 0.01-10 mol / L, and the molar ratio of the transition metal precursor to the organic carbon source precursor is 1:0.5-1:

4.

5. The application according to claim 1, characterized in that, The general formula of the nitro aromatic hydrocarbon compound is shown in formula (I): (I) Among them, (R) n This indicates that each of the n H atoms on the benzene ring is independently replaced by n identical or different R substituents, where n is 0, 1, 2, 3, 4, or 5. R can be nitro, amino, halogen, hydroxyl, alkyl, or alkoxy.

6. The application according to claim 1, characterized in that, The nitro aromatic compound is nitroanisole, 2-nitro-5-phenylmercaptoaniline, or o-nitroaniline.

7. The application according to claim 1, characterized in that, The reaction solvent for the hydrogenation reaction is one or more of water, methanol, ethanol, dimethyl sulfoxide, isopropanol and / or toluene, the pressure of the hydrogenation reaction is 0.4-6 MPa, and the reaction temperature is 50-300℃; or the molar ratio of the transition metal catalyst and the nitro aromatic compound is 1:1-1:200.

Citation Information

Patent Citations

  • Catalytic hydrogenation method of unsaturated compound

    CN114426490A

  • Method for preparing sulfo-arylamine through catalytic hydrogenation

    CN114426506A